Biomechanical research in gymnastics: What is done, what is needed - Prassas, S. (coachesinfo.com, 1999)
It is shown how many research project were carried out in gymnastics, what is needed and what has been found out for the different disciplines of gymnastics. Some commonly found concepts in biomechanical research as applied to gymnastics are listed.